2019
DOI: 10.18632/oncotarget.27204
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell reprogramming and lung cancer progression: a meta-analysis of transcriptome data

Abstract: Schwann cells were identified in the tumor surrounding area prior to initiate the invasion process underlying connective tissue. These cells promote cancer invasion through direct contact, while paracrine signaling and matrix remodeling are not sufficient to proceed. Considering the intertwined structure of signaling, regulatory, and metabolic processes within a cell, we employed a genome-scale biomolecular network. Accordingly, a meta-analysis of Schwann cells associated transcriptomic datasets was performed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Activated SCs have been shown to be present in a variety of cancers (18,(38)(39)(40)(41). We demonstrate that cancer cells activate SCs in a manner related to that seen after nerve injury and activate the transcription factor c-Jun.…”
Section: Discussionmentioning
confidence: 65%
“…Activated SCs have been shown to be present in a variety of cancers (18,(38)(39)(40)(41). We demonstrate that cancer cells activate SCs in a manner related to that seen after nerve injury and activate the transcription factor c-Jun.…”
Section: Discussionmentioning
confidence: 65%
“…In multiple types of cancer, such as thyroid cancer, salivary duct carcinoma, cutaneous squamous cell carcinoma, pancreatic cancer, and colon cancer, when the nerve is damaged or invaded by cancer cells, the number of GFAP-positive SCs increases [ 33 , 36 ]. Silva et al used bioinformatic analysis to investigate the transcriptomics of SCs among lung cancer samples and found that dedifferentiation-related pathways were overexpressed [ 56 ]. In cutaneous melanoma, the local neurodegenerative response caused by cancer is very similar to the nerve repair process induced by skin injury.…”
Section: Scs In the “Tumor-nerve Niche”mentioning
confidence: 99%
“…Among all of the residual effects, we observe that most of them are from methylation. For example, SLC2A1, ECT2, TNS4, DKK1, and GNPNAT1 are found to be associated with the survival of lung cancer patients [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Analysis Of Tcga Datamentioning
confidence: 99%